2009
DOI: 10.1108/09574090910954873
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the concept of supply chain resilience

Abstract: PurposeIn the emerging disciplines of risk management and supply chain management, resilience is a relatively undefined concept. The purpose of this paper is to present an integrated perspective on resilience through an extensive review of the literature in a number of disciplines including developmental psychology and ecosystems. In addition, the paper identifies and addresses some of the current theoretical gaps in the existing research.Design/methodology/approachSupply chain resilience has been defined by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
1,517
1
39

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,582 publications
(1,581 citation statements)
references
References 51 publications
24
1,517
1
39
Order By: Relevance
“…Ponomarov and Holcomb (2009) explained the urge for companies to have better understanding of resiliency in supply chains and logistics processes that can enable them to be competent of providing an efficient and effective response.…”
Section: What Is the Need Of Supply Chain Resilience?mentioning
confidence: 99%
See 2 more Smart Citations
“…Ponomarov and Holcomb (2009) explained the urge for companies to have better understanding of resiliency in supply chains and logistics processes that can enable them to be competent of providing an efficient and effective response.…”
Section: What Is the Need Of Supply Chain Resilience?mentioning
confidence: 99%
“…This is the essence of supply chain resiliency (Ponomarov and Holcomb, 2009). Colicchia et al (2010) suggested that organisations that respond quickly to disruptions have the prospect to coalesce their leadership position and this will help to build their brand value.…”
Section: What Is the Need Of Supply Chain Resilience?mentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of resilience has been traditionally studied in different disciplines, such as Ecology, Engineering, Psychology and Economics, but in the business context, the SC resilience concept is relatively new, and theoretical justifications are still in their infancy (Ponomarov & Holcomb, 2009;Juttner & Maklan, 2011;Ponis & Koronis, 2012: Soni, Jain, & Kumar, 2014. The key elements of SC resilience and the relationships among them are still poorly understood (Ponomarov & Holcomb, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The key elements of SC resilience and the relationships among them are still poorly understood (Ponomarov & Holcomb, 2009). The available literature on SC resilience is informative and is primarily focused on presenting several theoretical viewpoints of the phenomenon (Sheffi, 2001;Christopher & Lee, 2004;Christopher and Towill, 2001;Bhamra, Dani, & Burnard, 2011;Juttner & Maklan, 2011); more empirical studies are needed on the subject (Juttner & Maklan, 2011;Bhamra, Dani, & Burnard, 2011;Wieland & Wallenburg, 2013).…”
Section: Introductionmentioning
confidence: 99%